Carapaces of the Dnieper-Donets Basin as a New Exploration Target for significant hydrocarbon deposits - Petrovska, T.O.; Petrovskyi, O.P.; Tsikhovska, O.M.; Trachuk, A.Y. (Geofizicheskiy Zhurnal, 2022)
New geological structures — displaced blocks of salt overburden — were identified in the axial part of the Dnieper-Donets basin (DDB) beside one of the largest salt domes due to modern high-precision gravity and magnetic surveys and their joint 3D inversion with seismic and well log data. Superposition of gravity lineaments and wells penetrating Middle and Lower Carboniferous below Permian and Upper Carboniferous sediments in proximity to salt allowed proposing halokinetic model of displaced salt overburden, assuming Upper Carboniferoussalt reactivation. As an analogy todescribed halokinetic deformationswe consider rafts and carapaces of the US Gulf of Mexicobasin. Density of Carboniferous rocks within the displaced blocks evidence a high probability of hydrocarbon saturation. Possible traps include uplifted parts of the displaced blocks, abutting Upper Carboniferous reservoirs, and underlying Carboniferous sequence. Play elements (reservoir type and quality, seals, hydrocarbon generation) are analyzed using analogues from the Dnieper-Donets basin and the Gulf of Mexico basin. Hydrocarbon reserves of the displacedblocks within the study area are estimated to exceed Q50 (Р50)=150 million cubic meters of oil equivalent.